Sequential Mixed-Methods Study to Create a Model Framework to Identify Factors Predicting Parental Preparedness for Introduction of Child Artificial Intelligence Literacy Initiatives in Primary Schools in the United Kingdom - Nair, Malini (Digital Repository of Theses, 2024)
This dissertation used Sequential exploratory and subsequently sequential explanatory approach to answer a single research question to assess various predictors of parents’ preparedness for introduction of Child Artificial Intelligence Literacy (CAIL) initiatives in primary grades in UK schools. Study 1 comprises of initial qualitative exploration of the research question and identifying key variables of interest to predict parental CAIL preparedness. Study 2 tests the hypotheses using quantitative survey. 438 parents of primary kids in the UK participated. The outcomes of quantitative study were then further explained through qualitative Study 3 where 5 qualitative interviews were conducted. Stakeholder collaboration (parent-child, parent-teacher), a new variable thus far not fully used to assess parents within research context was developed. Together innovativeness, attitudes, collaboration predicted parents preparedness for CAIL while concerns did not predict CAIL well. Overall, the study model used new adapted scales and developed a new scale to assess collaboration. The study is the first of its kind to assess predictors of preparedness for CAIL among parents in the UK and provides a model that can be used to further research preparedness for CAIL or other new technologies. The results will help inform policy, researchers, educators as well as developers and curriculum design for CAIL.